2017
DOI: 10.1038/s41598-017-18007-4
|View full text |Cite
|
Sign up to set email alerts
|

Instagram, Flickr, or Twitter: Assessing the usability of social media data for visitor monitoring in protected areas

Abstract: Social media data is increasingly used as a proxy for human activity in different environments, including protected areas, where collecting visitor information is often laborious and expensive, but important for management and marketing. Here, we compared data from Instagram, Twitter and Flickr, and assessed systematically how park popularity and temporal visitor counts derived from social media data perform against high-precision visitor statistics in 56 national parks in Finland and South Africa in 2014. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
203
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 360 publications
(246 citation statements)
references
References 57 publications
8
203
0
6
Order By: Relevance
“…Social media derived from people sharing text or photos on an online platform, such as Flickr, has become particularly important for mapping recreation and aesthetic values appreciated by people in nature (Richards & Friess, 2015; van Zanten et al, 2016). Combining several content sharing platforms has been suggested for monitoring protected area popularity and temporal visitation patterns, using, for example, Instagram, Twitter and Flickr (Tenkanen et al, 2017). Active crowdsourcing, on the other hand, depends on users actively contributing with data through online platforms specifically designed to collect data about users or nature qualities (Ridding et al, 2018; Wolf, Brown, & Wohlfart, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social media derived from people sharing text or photos on an online platform, such as Flickr, has become particularly important for mapping recreation and aesthetic values appreciated by people in nature (Richards & Friess, 2015; van Zanten et al, 2016). Combining several content sharing platforms has been suggested for monitoring protected area popularity and temporal visitation patterns, using, for example, Instagram, Twitter and Flickr (Tenkanen et al, 2017). Active crowdsourcing, on the other hand, depends on users actively contributing with data through online platforms specifically designed to collect data about users or nature qualities (Ridding et al, 2018; Wolf, Brown, & Wohlfart, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While the use of social media data has been compared to visitor data on a regional scale previously (Graham & Eigenbrod, 2019; Tenkanen et al, 2017), spatial data and the values identified using passive and active crowdsourcing tools have not been extensively evaluated using the same location. One exception is Levin et al (2017) who compared the visitor density and values mapped by crowdsourcing tools in multiple protected areas.…”
Section: Introductionmentioning
confidence: 99%
“…material 1). Subsequently, generalised linear mixed models (GLMM), with a negative binomial distributon, were used in order to assess the influence of categorical and continuous fixed variables on the number of quests and favourite points, whilst keeping geocache type as a random variable (Fournier et al 2012, Skaug et al 2013. Given the influence of urban land cover on the quest and favourite points data (Results), the GLMM for protected areas, including both the geocache type and the intersecting land use land cover of the geocache,were included as a random variable.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies depart largely from the dominant perspectives on technology described earlier, and explore exploitation potentials for tourism organizations, as well as the correlations between tourists' posts, destination image and consumption patterns (e.g. Stepchenkova & Zhan, 2013;Rossi, Boscaro, & Torsello, 2018; Latorre-Mart ınez, Iñ ıguez-Berrozpe, & Plumed-Lasarte, 2014; Shuqair & Cragg, 2017;Tenkanen et al, 2017). To the best of the author's knowledge, no study has so far been published on social media in relation to nature-based tourism besides Tenkanen et al (2017).…”
Section: Instagram In Tourism Researchmentioning
confidence: 99%
“…Stepchenkova & Zhan, 2013;Rossi, Boscaro, & Torsello, 2018; Latorre-Mart ınez, Iñ ıguez-Berrozpe, & Plumed-Lasarte, 2014; Shuqair & Cragg, 2017;Tenkanen et al, 2017). To the best of the author's knowledge, no study has so far been published on social media in relation to nature-based tourism besides Tenkanen et al (2017). Most of the existing studies implement covert and/or quantitative data collection.…”
Section: Instagram In Tourism Researchmentioning
confidence: 99%